Growth type and motor performance in schoolboys - an international comparison - Mészáros, János (Acta Biologica Szegediensis, 2002)
The aim of the present study was to compare the growth type of 10-13-year-old non-athletic children living in different geographical regions, namely in Cyprus, Egypt, Hungary and Malaysia. Altogether 2,050 volunteer youngsters with less than 25% body fat content were investigated. Body build was estimated by the metric and plastic indices (Conrad 1963), and their cardiorespiratory endurance was assessed by the time of a 1,200 m run. The Hungarian boys were the tallest, and the Egyptians were the smallest, consistently. However, no consistent differences could be observed between the body mass means. The Hungarian boys could be characterised by the most negative metric index means, and the Cypriots were the most picnomorphs. Excluding the significant height differences from the variability of plastic index the consistent differences have disappeared. The most negative metric index means were found at 12 years of age in the Chinese, Cypriot and Egyptian samples, and the average metric indices have become greater consistently at the 13-year-old boys. The mean trend of growth type indices in Hungarian subjects has indicated a significant decrease in accordance with the data published earlier. By the cardiorespiratory endurance the subjects can be divided in two groups. Significantly better performances refer to the Cypriot and Hungarian subjects. The growth type indices introduced by Conrad (1963) sensitively reveal the slight differences in body built and physique resulting from ethnic differences, various physical activity, etc.